KAJIAN ERODIBILITAS TANAH PADA HULU DAS BATANG TARUSAN KABUPATEN PESISIR SELATAN - Marleni, Fitria; Drs. Dasrizal, MP, Drs. Dasrizal, MP; Prari Keslan, Widya (Pendidikan Geografi, 2014)
ABSTRACTThis study aims to determine soil characteristics (texture, structure, permeability, and organic matter), erodibility, and conservation efforts to reduce land degradation in the upstream watershed of Batang Tarusan Pesisir Selatan. The method used is descriptive. Areas in this study were taken based on the land use map as (Siguntur Tuo), shrub (Sungai Lundang), and mixed garden (Taratak). Determination of sample points is done by means of purposive sampling. Based on the results of data analysis this research findings that: lowest erodibility found in sample 1 (Taratak) with of 0,18, andthe highest in sample 2 (Lundang River) with value of 0,90 and slightly high in sample 3 (Siguntur Tuo) with a value of 0,43. Soil erodibility influence the erosion process, Taratak area, has small rate of erosion. this is because the value of 0,18 whit Lundang River area is very to erosion. Because erodibility value of 0,90. While Siguntur Tuo area vulnerable to erosion, due to the value of 0,43 erodibility. Referral conservation in the upstream watershed Tarusan is to have management of bench terraces, crop rotation and mulching.